1989
DOI: 10.1098/rspa.1989.0008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface-breaking cracks in metal sheets by using AC electric fields

Abstract: A surface-breaking crack in a metal sheet may be detected by passing an alternating current through the sheet and making measurements of the potential difference on the sheet’s surface. The distribution of potential on the metal surface depends on the exact geometry of the crack and the aim of this work is to predict the shape and size of a surface-breaking crack from the potential distribution. The theoretical model is formulated using the potential and streamfunction as the independent variables and the shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This uses the fact that dilation function (8), of the solution (v i−1 , q i−1 ) should be identical to the dilation function of the next solution (v i , q i ). Hence rather than using v i = 0 as prior information, we use v i = v i−1 instead for i ≥ 2.…”
Section: Multiple Transmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…This uses the fact that dilation function (8), of the solution (v i−1 , q i−1 ) should be identical to the dilation function of the next solution (v i , q i ). Hence rather than using v i = 0 as prior information, we use v i = v i−1 instead for i ≥ 2.…”
Section: Multiple Transmittersmentioning
confidence: 99%
“…The operator properties considered there are relevant to the analysis of eqns (1) and (2) here. Some approaches to Electrical Impedance Tomography (EIT) [7] and crack detection [8,9] also tackle inverse boundary problems for the Laplace equation. In 2D, conditional logarithmic stability estimates for the inverse boundary problem under a regularity assumption on the unknown boundary have been given [10,11], and this theoretical result has been extended to 3D by Cheng et al [12].…”
Section: The Inverse Problemmentioning
confidence: 99%
“…Once g(\jf) = Y(O,"'If) has been calculated, the shape of the crack in the physical plane is determined by evaluating X(O,'If) which is given by Mclver [3] as …”
Section: (7)mentioning
confidence: 99%
“…This formulation requires the stream function 'P along the top of the crack to be known. Using the Plemelj formulae Mciver [3] showed that this is given by…”
mentioning
confidence: 99%
“…(2) (3) In ferrous metals at relatively low frequencies, Lewis et al [2] showed that it is a reasonable approximation to assume that both the normal and tangential components of the electric field are continuous at the crack edge and so the potential distribution in the plane of the crack is an analytic continuation of the potential distribution on the upper surface of the metal. Thus, the crack face may be 'unfolded' into the same plane as the metal surface resulting in a two dimensional boundary value problem for a single potential in a region with a partially unknown boundary, as illustrated in figure 1.…”
mentioning
confidence: 99%